Impact of COVID-19 on Ocular Surface Health: Infection Mechanisms, Immune Modulation, and Inflammatory Responses - Duliurui Huang; Weixia Xuan; Zhijie Li (Viruses)
COVID-19, caused by SARS-CoV-2, has presented formidable challenges to global health since its emergence in late 2019. While primarily known for respiratory symptoms, it can also affect the ocular surface. This review summarizes the effects of SARS-CoV-2 on ocular surface immunity and inflammation, focusing on infection mechanisms, immune responses, and clinical manifestations. Ocular symptoms, though uncommon, include conjunctivitis, dry eye, and blurred vision. SARS-CoV-2 binds to ACE2 receptors in ocular surface epithelial cells, facilitating viral entry, replication, and local dissemination. The innate immune responses involving corneal epithelial cells and immune cells are discussed, alongside mechanisms of antigen presentation and adaptive immunity. The review also examines the roles of cytokines and chemokines in mediating ocular surface inflammation and explores the impact of cytokine storms and chronic inflammation on ocular health. Additionally, the interplay between systemic and ocular immune responses is highlighted, analyzing how systemic COVID-19 inflammation influences ocular surface health. These insights underscore the broader implications of COVID-19 beyond localized ocular infection. By consolidating current findings, this review aims to guide preventive and therapeutic strategies while identifying directions for future research to mitigate the ocular consequences of COVID-19.